UWEC Marketing Program Brand Audit - Swanson, Scott R.; Nechkash, Samuel; Schwonke, Mitchell (My University, 2017)
The purpose of the brand audit of the UW-Eau Claire Marketing Program is to capture current students' perceptions and level of satisfaction of various attributes of the program. This information will be used to help set strategic direction for the marketing area.
Color poster with text and bar graphs.
Keywords: Brand audit; Posters; Marketing